First record of eumops perotis (Schinz, 1821) (Chiroptera, molossidae) from the Cerrado of Mato Grosso do Sul, Central-West Brazil - Torres, Jaire Marinho; Porfirio, Grasiela Edith de Oliveira; Ikeda, Priscila [UNESP]; Bordignon, Marcelo Oscar; Santos, Filipe Martins; Elisei, Carina (Pensoft Publishers, 2020)
The Greater Bonneted Bat, Eumops perotis (Schinz, 1821), is widely distributed in Brazil, but valid records of its oc-currence in Mato Grosso do Sul, Central-West Region, are still scarce and limited to the Pantanal portion of the state. Here, we report the first record of E. perotis from the Cerrado portion of Mato Grosso do Sul, based on specimens collected in an urban forest remnant in the municipality of Campo Grande. These specimens add to the records of E. perotis in the Cerrado of the Central-West and fill gaps in the distribution of this species.
Keywords: Distribution; Greater Bonneted Bat; South America